2018
DOI: 10.1159/000491716
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA8924 Promotes Cervical Cancer Cell Proliferation, Migration and Invasion by Competitively Binding to MiR-518d-5p /519-5p Family and Modulating the Expression of CBX8

Abstract: Background/Aims: Circular RNAs (circRNAs) play a significant role in the development and progression of various human cancers. However, the expression and function of circRNAs in cervical cancer (CC) have rarely been explored. The aim of this study was to investigate the biological function of circRNA8924 in CC and elucidate the possible molecular mechanism involved. Methods: Quantitative polymerase chain reaction was used to determine mRNA expression of circRNA8924, miR-518d-5p/519-5p and CBX8 in CC tissues a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 36 publications
1
68
0
Order By: Relevance
“…CSX8 is known as a member of CBX family and exerts oncogenic functions in some cancers. Liu et al reported that CBX8 could be regulated by miRNAs (miR-518d-5p/519-5p) at post-transcriptional level [25]. In hepatocellular carcinoma, CBX8 exhibits oncogenic properties by affecting AKT/β-catenin pathway [26].…”
Section: Discussionmentioning
confidence: 99%
“…CSX8 is known as a member of CBX family and exerts oncogenic functions in some cancers. Liu et al reported that CBX8 could be regulated by miRNAs (miR-518d-5p/519-5p) at post-transcriptional level [25]. In hepatocellular carcinoma, CBX8 exhibits oncogenic properties by affecting AKT/β-catenin pathway [26].…”
Section: Discussionmentioning
confidence: 99%
“…Persistent infection with high-risk human papillomavirus (HPV) has been verified as the major risk factor in cervical cancer progression (Liu et al, 2018). More than 118 different types of HPV has been validated and the type of HPV 16 and 18 attributed to three quarters incidence rates (Crosbie et al, 2013).…”
Section: Cell Line and Culturementioning
confidence: 99%
“…For instance, circ_8924 was reported by Li W to promote the CC cell proliferation, migration and invasion by sponging miR-518e-5p family and regulating the expression of CBX8. 20 Moreover, results from Xianchao Kong el al showed that circ101996 might act as an oncogene of CC through increasing the expression of TPX2 through miR-8075. 21 In this study, a circRNA microarray analysis was conducted on two CC-associated circRNA GSE datasets (GSE102686 and GSE113696) downloaded from the GEO database (www.ncbi.nlm.nih.gov/geo) to screen specific circRNAs that might involve in the pathogenesis of CC.…”
Section: Discussionmentioning
confidence: 99%